Slow progression: Educational trajectories of young men and women in Ethiopia - Yisak, T; Tiumelissan, A (Young LIves, 2021)
As children, the young women and men in the Young Lives study often had high aspirations for their lives after school, but many have found themselves unable to fulfil their dreams. Drawing on Young Lives longitudinal qualitative and survey data in Ethiopia, this working paper finds that more than half of the young people in the study dropped out of school early and that many students are older than the intended age for their school year. Because of their prolonged school trajectories, several are still attending school as adults. Only one has completed university education. Prolonged educational trajectories also mean young women are susceptible to marriage before finishing school